Classroom strategies for dealing with some difficulties in the Caribbean Examinations Council's chemistry syllabus in St. Kitts-Nevis secondary schools - Williams, Clement D. O. (1984)
This study sought to examine some of the difficulties presented to both teachers and students by the introduction of the Caribbean Examinations Council's (CXC) Secondary Education Certificate General Proficiency in Chemistry. It concentrates on: 1) the conceptual difficulties to be faced by students in understanding such topics as (a) the mole and molarity, (b) electrochemistry, and (c) ionic equations; and 2) the problems expected to be experienced by teachers in finding suitable materials to teach the section of the syllabus on Industrial Chemistry. The study offers some strategies for use by teachers in dealing with most of the difficulties expected to be experienced in using the syllabus
Keywords: Secondary school curriculum